2020
DOI: 10.7150/jgen.51181
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequences for the Frankia sp. strains CgS1, CcI156 and CgMI4, Nitrogen-Fixing Bacteria Isolated from Casuarina sp. in Egypt

Abstract: Frankia sp. strains CgS1, CcI156 and CgMI4 were isolated from Casuarina glauca and C. cunninghamiana nodules. Here, we report the 5.26-, 5.33-and 5.20-Mbp draft genome sequences of Frankia sp. strains CgS1, CcI156 and CgMI4, respectively. Analysis of the genome revealed the presence of high numbers of secondary metabolic biosynthetic gene clusters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…Especially, genomic and transcriptomic tools have shown significant potential to understand the actinomycetes-plant symbiotic interaction considering microbial natural product biosynthesis, metabolic diversity, stress tolerance, and so on [119]. Interestingly, approximately 61 Frankia genomes have been sequenced and are currently available at Genome Information by Organism, NCBI [11,12,15,17,19,54,[119][120][121][122]. An in silico study on 21 strains of Frankia identified that all genomes possessed genes for the biosynthesis of auxins, cytokinins, siderophores, and nitrogenases [76].…”
Section: Cell Signalling and Functional Genomics Of Actinomycetes-pla...mentioning
confidence: 99%
See 1 more Smart Citation
“…Especially, genomic and transcriptomic tools have shown significant potential to understand the actinomycetes-plant symbiotic interaction considering microbial natural product biosynthesis, metabolic diversity, stress tolerance, and so on [119]. Interestingly, approximately 61 Frankia genomes have been sequenced and are currently available at Genome Information by Organism, NCBI [11,12,15,17,19,54,[119][120][121][122]. An in silico study on 21 strains of Frankia identified that all genomes possessed genes for the biosynthesis of auxins, cytokinins, siderophores, and nitrogenases [76].…”
Section: Cell Signalling and Functional Genomics Of Actinomycetes-pla...mentioning
confidence: 99%
“…Other studies reported several genes resistant to salt stress from Frankia strains, which were associated with hypothetical proteins. Also, several secondary metabolic biosynthetic gene clusters for metabolic potential as natural product profiles and secondary metabolites pathways were prevalent in different strains [12,120,186]. Different studies reported physiological and biochemical adjustments of actinorhizal plants under salt stress, leading to a sharp decrease in nitrogenase reductase and nitrogenase activities, and impairment of ammonium assimilation pathway in Frankia [187,188].…”
Section: Abiotic Stress Anthropogenic Influences and Actinorhizal Sym...mentioning
confidence: 99%